Bioenergetics and intermuscular fat in chronic obstructive pulmonary disease‐associated quadriceps weakness. Issue 2 (19th November 2014) - Shields, Gregory Samuel; Coissi, Graziele S.; Jimenez‐Royo, Pilar; Gambarota, Giulio; Dimber, Rahul; Hopkinson, Nicholas S.; Matthews, Paul M.; Brown, Andrew P.; Polkey, Michael I.
ABSTRACT Introduction: Chronic obstructive pulmonary disease (COPD) is associated with metabolic abnormalities in muscles of the lower limbs, but it is not known whether these abnormalities are generalized or limited to specific muscle groups, nor is there an easy way of predicting their presence. Methods: Metabolism in the quadriceps and biceps of 14 COPD patients and controls was assessed during sustained contraction using 31‐phosphorus magnetic resonance spectroscopy (31P MRS). T1 MRI was used to measure quadriceps intermuscular adipose tissue (IMAT). Results: COPD patients had prolonged quadriceps phosphocreatine time (patients: 38.8 ± 12.7 s; controls: 25.2 ± 10.6 s; P = 0.006) and a lower pH (patents: 6.88 ± 0.1; controls: 6.99 ± 0.06; P = 0.002). Biceps measures were not significantly different. IMAT was associated with a nadir pH <7.0 (area under the curve = 0.84). Conclusions: Anaerobic metabolism during contraction was characteristic of quadriceps, but not biceps, muscles of patients with COPD and was associated with increased IMAT. Because IMAT can be assessed quickly by conventional MRI, it may be a useful approach for identifying patients with abnormal muscle bioenergetics. Muscle Nerve 51: 214–221, 2015